NUTRITION EDUCATION “FILL MY PLATE” FOR STUDENTS AT ELEMENTARY SCHOOL JATINANGOR, SUMEDANG, WEST JAVA - Bambang Aditya Nugraha Bambang Aditya Nugraha; Sulastini Sulastini; Sandra Pebrianti Sandra Pebrianti; Adelia F Fauzi Adelia F Fauzi; Alifa A Putri Alifa A Putri; Dervan S Rosadi Dervan S Rosadi; M T Bahtiar M T Bahtiar; Unais Zamzami Unais Zamzami; Nabila S Ramadani Nabila S Ramadani; Nathania A Trixie Nathania A Trixie; Najwa Sabrina Najwa Sabrina; Regatta A Dharma Regatta A Dharma; Tiara A Mazaya Tiara A Mazaya; Zahwa Z Lazuardy Zahwa Z Lazuardy (Jurnal Pengabdian Masyarakat DEDIKASI, 2024)
Elementary school students require adequate nutrition to supportlearning process, growth and development. Adequate nutritionallows students to have good academic achievement and avoidnutritional problems such as malnutrition and obesity. Therefore, anutritional education program for students entitled fill my plate wascarried out. This education contains a "isi piringku/fill my plate"nutritional guide compiled by Indonesia government to replace"empat sehat lima sempurna/four healthy 5 perfect" which hasbeen launched since 1952’s so it is considered outdated. Thepurpose of this program is to increase students' knowledgeregarding the nutrition needed every day in order to support theiractivity. The activity method consists of pre-test, lecture, fun gamesand post-test. This activity was attended by 30 6th grade studentsof Kananga Jatinagor Elementary School. This school was chosenbecause it is located in a suburban area which is at risk of havinglimited access to information and is far from the district city center.The results of the program showed that most students were able tore-explain the material that had been delivered. This activity isrecommended to be carried out periodically in each grade, not onlyin grade six.